EFFECTS OF WATER QUALITY, pH AND STATE OF THE MEDIUM ON GROWTH AND DEVELOPMENT OF COCONUT EMBRYOS IN VITRO - M.B.B. Areza; E.P. Rillo; C.A. Cueto; A.W. Ebert; O.D. Orense (International Coconut Community Journal, 1995)
The effects o f the quality qfwater, pH and state qf the medium on growth and development of coconut embryos in vitro were evaluated. Germination of embryos in Y3 liquid medium was not affected by neither wau ,r quality nor pH adjustment. These suggest that tap water could replace glass distilled water and gelling agent could be eliminated in embryo culture qf coconut. However, pH qf the medium has to he adjusted.